Nine Important Steps to Maintain the Health of Adult Women - Rubianti, Rubianti; Ewildan, Ewildan; Munzirin, Reni Mardika (Research of Service Administration Health and Sains Healthys, 2024)
Adult women's health is an important topic that impacts quality of life and overall well-being. Women face unique health challenges, so understanding and implementing important steps to maintain their health is critical. This research aims to identify nine important steps that can help adult women maintain their health optimally. This research used a descriptive qualitative approach with in-depth interviews with 30 adult women aged 25-55 years. Participants were selected using purposive sampling based on their diverse backgrounds and health conditions. Data was collected through semi-structured interviews and analyzed using thematic analysis methods to identify main themes related to important steps in maintaining the health of adult women. Data analysis revealed nine important steps that significantly contribute to adult women's health: (1) a healthy and balanced diet, (2) regular exercise, (3) regular health check-ups, (4) stress management, (5) adequate sleep, (6) adequate hydration, (7) maintaining mental health through social support, (8) avoiding bad habits such as smoking and excessive alcohol consumption, and (9) self-education about health. This research concludes that these nine steps are the key to maintaining Holistic adult women's health. Implementation of these steps can improve quality of life, prevent chronic disease, and promote overall well-being. Education and awareness about the importance of these measures should be increased through public health programs and support from the health community.